Genre on time. Fiction film framings of scandalous politics in Denmark since 2001 - Givskov, Cecilie (Northern Lights: Film & Media Studies Yearbook, 2009)
In Denmark the political fiction film has not been at the centre of attention for film-makers, and when it has been explored it has in fact not been a very successful genre. However, recently, an interest in the political sphere has emerged among film-makers in Denmark. Simultaneously, the political culture in Denmark since the turn of the century has become less focused on a welfare and solidarity consensus, and it has created new types of conflicts where the population has become more sceptical towards the political system and also towards the journalistic credo. The article shows how the socio-cultural political context developed especially since 2001 interacts with the content and form of political fiction films, and how the films are embedded in a general mediatization of culture which implies that subject matter related to, for example, politics is framed in popular form in news and in fiction films.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9ubC43LjE1M18x